Pharmacokinetics and dosing estimation of meropenem in Japanese patients receiving continuous venovenous hemodialysis. Issue 6 (June 2015) - Kawano, Shinji; Matsumoto, Kazuaki; Hara, Ryohei; Kuroda, Yuko; Ikawa, Kazuro; Morikawa, Norifumi; Horino, Tetsuya; Hori, Seiji; Kizu, Junko
Abstract: The pharmacokinetics of meropenem have not yet been examined in Japanese patients receiving Continuous venovenous hemodialysis (CVVHD). The aim of this clinical investigation was to determine the pharmacokinetic parameters of meropenem in critically ill patients receiving CVVHD in order to estimate dosing regimens for the patient population in Japan. The values of pharmacokinetic parameters were 17.5 ± 5.6 l for V1, 1.27 ± 0.38 h −1 for K12, 0.71 ± 0.40 h −1 for K21 and 0.17 ± 0.02 h −1 for K10 . Based on these mean parameters (V1, K12, K21 and K10 ), time above MIC (T > MIC) values were estimated at different MICs using various meropenem regimens. For bacteria with a meropenem MIC of ≤2 μg/ml, a dosing regimen of 0.25 g every 24 h achieved more than 40% T > MIC. For a MIC of 4 μg/ml, all the regimens tested, except for 0.25 g every 24 h, achieved more than 40% T > MIC. For a MIC of 16 μg/ml, dosing regimens of 0.5 g every 8 h, 1 g every 12 h, and 1 g every 8 h achieved 40% T > MIC, reaching the pharmacokinetic-pharmacodynamic target range. This is the first study to examine the pharmacokinetics of meropenem under a CVVHD setting in Japan. The pharmacokinetic-pharmacodynamic profile of dosing regimens tested in this study will assist in selecting the appropriate meropenem regimens for patients receiving CVVHD.